Validation of Teaching and Learning Guiding Principles Instrument for Malaysian Higher Learning Institutions - Nurulhuda Abd Rahman; Azwani Masuwai; Norâ€™ain Mohd Tajudin; Ong Eng Tek; Mazlini Adnan (UUM Press, 2016)
Purpose â€" This study was aimed at establishing, through the validation of the Teaching and Learning Guiding Principles Instrument (TLGPI), the validity and reliability of the underlying factor structure of the Teaching and Learning Guiding Principles (TLGP) generated by a previous study.   Method â€" A survey method was used to collect data through the 67-item TLGPI. The TLGPI was hypothesised to measure the six constructs of the TLGP. The TLGPI was administered online to all academicians from 20 public universities in Malaysia. In total, 284 responses were received from a population of 31,608 academicians. The collected data were subjected to a Confirmatory Factor Analysis to test for construct reliability, model fit, and convergent validity of each contructâ€™s measurement model. The CFA was also used to test the model fit and the discriminant validity of the pooled measurement model.   Findings â€" The CFA supported a finalised measurement model of six constructs for the TLGP. The TLGP was found to have reliable and valid constructs that represented the aspects of teaching and learning that are important in Malaysian higher learning institutions.   Significance â€" This pioneer study is vital in the Malaysian higher education context since the development of teaching and student learning can benefit from a set of empirically validated teaching and learning principles. The TLGP are statements on the scholarship of teaching and learning and can be a reference guide to good practice that can help set the pathway to a high-quality learning environment for students in the Malaysian higher learning institutions and the wider Asian context.